A Analisis Kreativitas Siswa Dalam Mendesain Komik Dengan Model Pembelajaran Project Based Learning (PJBL) Di Sanggar Belajar Kepong Malaysia - Irianti Yuliana, Irianti; Saragih, Mandra (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to analyze students' creativity in designing comics using the Project Based Learning (PjBL) learning model at the Kepong Learning Studio, Malaysia. Student creativity is evaluated based on 3 aspects, namely originality, flexibility and elaboration in designing comics. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. The research results show that the application of the PjBL model has a positive impact on the development of student creativity. Students are more active in exploring ideas, producing more innovative comic designs, and improving critical thinking and collaboration skills in completing projects. The main supporting factor is the use of project-based methods which encourage students to be more independent in the learning process. However, researchers also found several obstacles, such as limited technical skills in drawing and using digital design applications. The conclusion of this research confirms that PjBL is effective in increasing students' creativity in designing comics. The recommendation from this research is the systematic application of the PjBL method and increased guidance in the use of digital design technology to support the development of student creativity.